Exploration of the causes of cerebrospinal fluid leakage after endoscopic endonasal surgery for sellar and suprasellar lesions and analysis of risk factors - Xiong, Yicheng; Liu, Yajing; Xin, Guo; Xie, Shenhao; Luo, Hai; Xiao, Liming; Wu, Xiao; Hong, Tao; Tang, Bin (Frontiers in Surgery, 2022)
Objective: Postoperative cerebrospinal fluid (CSF) leakage following endoscopic endonasal surgery (EES) is a frequent complication. This study aims to identify potential risk factors of postoperative CSF leakage. Methods: A retrospective review of 360 patients who underwent EES was included. The associations between postoperative CSF leakage and patient demographics, medical history, tumor characteristics, and intraoperative repair techniques were analyzed, the diagnosis and repair of postoperative CSF leakage were also introduced. Results: Postoperative CSF leakage occurred in 14 patients (3.9%), 2 of them cured by lumbar cistern drainage (LD), 12 underwent endoscopic repair. Among these 12 cases, 3 cases were repaired twice, and the rest were cured at first repaired. During the repair surgery, 1 case detected insufficient embedded fat, 7 cases with breached inner artificial dura, 3 had vascularized pedicle nasoseptal flap (VP-NSF) displacement, 2 cases with VP-NSF perforation, 2 cases with VP-NSF inactivation and 1 case with imperfect adherence of VP-NSF to the skull base. 8 cases had intracranial infections. Exclude 1 case who died of severe intracranial infection, the rest were cured and discharged without obvious sequelae. Multivariate analysis revealed that the suprasellar lesion, subarachnoid invasion, and intraoperative Grade 3 flow CSF leakage were the risk factors of CSF leakage after operation, while the bone flap was a protective factor. Conclusion: Bone flap combined with VP-NSF and iodoform gauze for skull base reconstruction is recommended in high-risk patients, while postoperative lumbar cistern drain remains dispensable.